2012
DOI: 10.1155/2012/176108
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Evolved Glyphosate Resistance in a North Carolina Palmer Amaranth (Amaranthus palmeri) Biotype

Abstract: Inheritance of glyphosate resistance in a Palmer amaranth biotype from North Carolina was studied. Glyphosate rates for 50% survival of glyphosate-resistant (GR) and glyphosate-susceptible (GS) biotypes were 1288 and 58 g ha−1, respectively. These values for F1 progenies obtained from reciprocal crosses (GR×GSandGS×GRwere 794 and 501 g ha−1, respectively. Dose response of F1 progenies indicated that resistance was not fully dominant over susceptibility. Lack of significant differences between dose responses fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 29 publications
5
68
1
1
Order By: Relevance
“…In the Georgia A. palmeri population, the EPSPS gene was present on all chromosomes. Subsequently, a North Carolina GR A. palmeri population was reported with EPSPS gene duplication from 22‐ to 63‐fold . A New Mexico GR A. palmeri population was sevenfold more resistant than a GS population and had EPSPS gene duplication ranging from two‐ to tenfold, and individuals with EPSPS gene duplication were able to survive label‐rate glyphosate applications (0.82 kg ha −1 ) …”
Section: Gene Duplicationmentioning
confidence: 99%
“…In the Georgia A. palmeri population, the EPSPS gene was present on all chromosomes. Subsequently, a North Carolina GR A. palmeri population was reported with EPSPS gene duplication from 22‐ to 63‐fold . A New Mexico GR A. palmeri population was sevenfold more resistant than a GS population and had EPSPS gene duplication ranging from two‐ to tenfold, and individuals with EPSPS gene duplication were able to survive label‐rate glyphosate applications (0.82 kg ha −1 ) …”
Section: Gene Duplicationmentioning
confidence: 99%
“…Several studies related to glyphosate resistance and elevated EPSPS copy number in Palmer amaranth and related species are available [18,22,31,42,43]. Elevated EPSPS copy number has also been identified as a glyphosate resistance mechanism in ryegrass [40].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the target-site mechanism of resistance detected in Eleusine indica and the selective sequestration of glyphosate into vacuoles (non-target site mechanism) observed in C. canadensis would be similarly inherited (Ng et al, 2004b;Ge et al, 2010). On the other hand, the variable number of EPSPS copies explains the different glyphosate sensitivities in resistant A. palmeri and could influence the type of glyphosate resistance inheritance, determining whether it is monogenic or polygenic (Chandi et al, 2012;Mohseni-Moghadam et al, 2013).…”
Section: Cross-breedingmentioning
confidence: 99%
“…Several authors found that resistance to glyphosate is controlled either by single genes with different levels of dominance (Ng et al, 2004a;Zelaya et al, 2004;Wakelin and Preston, 2006) or by multiple genes (Simarmata et al, 2005;Chandi et al, 2012). This information is particularly relevant in understanding and modelling the evolution of resistance (Gressel and Segel, 1978;Neve et al, 2011).…”
Section: Introductionmentioning
confidence: 99%